2009
DOI: 10.3200/35-08-091
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Attentional Focusing during Finger Movements: A fMRI Study

Abstract: One finding in recent motor control and learning research is that an external focus (i.e., attending to environmental aspects) improves performance, whereas an internal focus (i.e., controlling bodily movements) impedes it. Despite being replicated in behavioral studies, the neurophysiological basis of this phenomenon remains largely unknown. The present authors separate global attention to actions into an external and an internal focus. Using a between-participants design, participants were either trained to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
2
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 27 publications
4
58
2
5
Order By: Relevance
“…Greater activation of the primary somatosensory, motor, and insular cortices were observed when externally compared to internally focused instructions were utilized during the acquisition of a simple motor skill (key press sequence; Zentgraf et al, 2009). Whilst an external focus enhanced task-relevant tactile information processing necessary for the effective execution of environmental-outcome movements, internally focused instructions disrupted the efficient neural flow between sensory and motor areas.…”
Section: Discussionmentioning
confidence: 99%
“…Greater activation of the primary somatosensory, motor, and insular cortices were observed when externally compared to internally focused instructions were utilized during the acquisition of a simple motor skill (key press sequence; Zentgraf et al, 2009). Whilst an external focus enhanced task-relevant tactile information processing necessary for the effective execution of environmental-outcome movements, internally focused instructions disrupted the efficient neural flow between sensory and motor areas.…”
Section: Discussionmentioning
confidence: 99%
“…computer work and playing music. Furthermore, the task is widely applied in studies of both healthy individuals (Hammond & Gunasekera, 2008;Hansen & Ohnstad, 2008;Sundqvist, Johnels, Lindh, Laakso, & Hartelius, 2015;Wing & Kristoffersen, 1973;Zentgraf et al, 2009) and in patients with e.g. Parkinson's disease (Shima, Tamura, Tsuji, Kandori, & Sakoda, 2011;Teo, Rodrigues, Mastaglia, & Thickbroom, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…To address this question, research has started to elucidate the underlying mechanisms mediating the effects of these two attentional foci (e.g., Zentgraf and Munzert, 2009; Wulf and Lewthwaite, 2010). Using functional magnetic resonance imaging (fMRI), Zentgraf et al (2009), for example, explored the brain structures involved in finger movements by comparing the two distinct attentional foci in a between-subject design. They observed an increase in blood oxygen level dependent (BOLD) response under an external focus of attention in the primary motor cortex, primary somatosensory cortex, and the insular region of the left hemisphere.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that these findings reflected augmented sensory processing of tactile information when focusing externally on the buttons, which had to be pressed without visual control in the finger-moving task. Further, Zentgraf et al (2009) propose more specifically that this augmented sensory processing had led to a modulation of integration mechanisms in neural sensorimotor systems. To our knowledge, however, the brain regions involved in switching from an internal attentional focus on movement to an external or vice versa have yet to be examined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation